Analyzing input quality along three dimensions: interactive, linguistic, and conceptual. Issue 1 (31st January 2020) - ROWE, Meredith L.; SNOW, Catherine E.
Abstract: This paper provides an overview of the features of caregiver input that facilitate language learning across early childhood. We discuss three dimensions of input quality: interactive, linguistic, and conceptual. All three types of input features have been shown to predict children's language learning, though perhaps through somewhat different mechanisms. We argue that input best designed to promote language learning is interactionally supportive, linguistically adapted, and conceptually challenging for the child's age/level. Furthermore, input features interact across dimensions to promote learning. Some but not all qualities of input vary based on parent socioeconomic status, language, or culture, and contexts such as book-reading or pretend play generate uniquely facilitative input features. The review confirms that we know a great deal about the role of input quality in promoting children's development, but that there is much more to learn. Future research should examine input features across the boundaries of the dimensions distinguished here.